Climate-smart forest management caught between a rock and a hard place - Muys, Bart; Messier, Christian (Annals of forest science., 2023)
Key message The UNFCCC COP 27 in Sharm El-Sheikh confirmed that climate policies too heavily rely on climate mitigation by forests rather than on de-fossilizing the energy system, to keep global warming within the safe 1.5 °C. Reliable mitigation by forests would imply healthy productive forests well adapted to climate change, and this is no longer the case. The current trend in loss of forest vitality shows that the adaptation of forests is urgently needed, but measures are being insufficiently adopted by foresters on the ground. In this letter, we wonder about the reasons for this inaction paralyzing climate-smart forestry and propose a way forward using a diversity-based no-regret approach in line with available knowledge.